2018
DOI: 10.3390/en11010228
|View full text |Cite
|
Sign up to set email alerts
|

How Do Chinese Residents Expect of Government Subsidies on Solar Photovoltaic Power Generation?—A Case of Wuhan, China

Abstract: This paper investigates local residents' expectations of the Chinese government subsidies on solar photovoltaic (PV) power generation. Residents' demographics including age, educational attainment, income level, gender, and employment fields are analyzed based on a survey study in Wuhan, China. Results of the regression analysis on the influence of demographic variables on residents' expectations indicate that: (1) residents with different demographics have significantly different expectations of the Chinese g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A PV system is easier to operate than a diesel generator as compared to an alternative electrical energy source. This system is capable of reducing running costs, requires low maintenance, and exerts minimal environmental impact [ 17 ]. The last few years have witnessed the significant maturity of PV technology, which enabled the standardization of modular components.…”
Section: Stand-alone Photovoltaic Systemmentioning
confidence: 99%
“…A PV system is easier to operate than a diesel generator as compared to an alternative electrical energy source. This system is capable of reducing running costs, requires low maintenance, and exerts minimal environmental impact [ 17 ]. The last few years have witnessed the significant maturity of PV technology, which enabled the standardization of modular components.…”
Section: Stand-alone Photovoltaic Systemmentioning
confidence: 99%
“…The angle correction factor (R t ) should be considered when calculating the direct solar radiation received by the solar photovoltaic modules because of the influence of the angle between the normal vector of the solar photovoltaic modules and the direction vectors of the solar rays. R t can be expressed as Equation (9) [43,44]:…”
Section: Calculation Of S T and R Tmentioning
confidence: 99%
“…However, PV potential map is the precondition and foundation of large-scale development of PV. China has a vast territory and abundant solar resources, making it an appropriate country to develop and utilize solar energy resources [9]. The China National Energy Administration announced that the government aimed to reach the capacity of 100 GW of solar photovoltaic by 2020 in its 13th Five-Year Plan.…”
Section: Introductionmentioning
confidence: 99%
“…The research by Ding showed that residents in different regions have different expectations for photovoltaic power generation facilities. The government should adopt useful policies to promote photovoltaic projects according to local conditions [22].…”
Section: Introductionmentioning
confidence: 99%